Tectono-metamorphic evolution of the Embu Terrane and the adjacent terranes at the Southern Ribeira Belt - Cabrita, Dina Isabel Guerreiro (2022)
Metamorphism coupled with magmatism and deformation provides key information in understanding the evolutionary tectonic setting of orogenic belts. This study is particularly important in Neoproterozoic Ribeira Belt, where there are currently contrasting tectonic models. Models involving multiple long-lived terrane accretion have been the most accepted until recently. However, recent studies propose an intracontinental setting model for the belt. The Embu Terrane and the adjacent units are crucial areas to investigate the above controversial models once it represents a major unit within Ribeira Belt. For this purpose, this thesis investigated the geotectonic evolution of Embu Terrane, the adjacent northwestern Votuverava Group and the Embu Terrane southeastern limit, the crustal-scale Cubatão Shear Zone by a multi-method study involving whole-rock and mineral chemical analysis, quartz crystallographic fabric analysis, and petrochronology. The data in this contribution reveal a distinct evolutionary history between the Votuverava Group and Embu Terrane. Mafic igneous rocks from the Votuverava Group record the existence of two Mesoproterozoic magmatic events at (1490-1475 Ma and 1300-1260 Ma), which are characterized by Th / Yb ratios above N-MORB, low Ta / Yb and Nb / La ratios, low Nb and Zr concentrations, negative Nb anomaly, Ndt of -3 to +6, an Nd TDM model age between 2110-1500 Ma, which are characteristics of arc-related magmatism. In the Embu Terrane, a third magmatic event is recorded during the Neoproterozoic (900 Ma) with tholeiitic mafic rocks characterized by low enrichments in LREE, negative Nb anomaly, low Nb and Zr contents and low Nb / La and Zr /Y ratios, consistent with arc-related basalts. Additionally, the metamorphic data from the Embu Terrane metasedimentary rocks demonstrated a high-grade metamorphic event between 810760 Ma represented by sillimanite, sillimaniteK-feldspar, and cordierite zones. Petrochronological data indicate that the high-grade metamorphic rocks within the Embu Terrane attained conditions between 750805 °C and 3.69.2 kbar, concomitant with igneous activity recorded during this period. Finally, petrochronological data from the crustal-scale Cubatão Shear Zone indicated medium-temperature conditions of 460520 °C and 4.59.5 kbar, consistent with quartz recrystallization microstructures indicative of subgrain rotation recrystallization between 610570 Ma. The CSZ activity is coeval with the main period of activity of other ductile shear zones from the Ribeira Belt. This period coincides with the main period of other regional shear zones activity, voluminous granitic magmatism, and regional metamorphism in the Ribeira Belt, indicating active participation of the transcurrent shear zones in the orogenic processes. The data in this contribution record multiple periods of accretion and convergence settings and, therefore, is not consistent with a single intracontinental evolutionary setting.